Application of the customs procedure of processing in the customs territory when performing foreign trade operations - E. A. Lysenko; S. V. Fomin (Вестник университета)
The relevance of the research topic lies in the fact that the customs procedure of processing in the customs territory, which allows the use of imported goods in products manufacture for export without paying customs duties and taxes, becomes the object of close attention of foreign economic activity participants, causing both a high level of interest from the economic point of view and certain difﬁculties associated with its application in foreign trade. The purpose of the study is to conduct an economic and statistical analysis of the application of the customs procedure of processing in the customs territory and to propose ways to improve it. The tasks to achieve the goal were: analyzing the theoretical and legal foundations of the customs procedure application, analyzing its application, identifying the customs control stages over its application, identifying problematic aspects in its use, and proposing ways to solve them. When performing the tasks, the following general scientiﬁc methods were used: observation, induction and deduction, and collection and analysis of statistical data. As the study result, conclusions have been formulated based on the results of economic and statistical analysis of the application of the customs procedure of processing in the customs territory, the customs control stages over its application have been identiﬁed, the directions in which problems arise in the procedure application have been revealed, and proposals for their solution have been developed.